The levelized cost of energy in the presence of uncertainty on the offshore wind speed - J. Pablo Arenas-López; Mohamed Badaoui (Heliyon)
In the last few years, offshore wind power has experienced remarkable growth attributable to the need to mitigate the impact of global warming, which leads to policies for reducing greenhouse gas emissions and fostering investment in renewable technologies. However, this endeavor raises concerns regarding economic assessment studies, where the levelized cost of energy (LCOE) is the most widely adopted index. This paper aims to propose an estimation of the LCOE under generation uncertainty induced by the intermittency of the wind and thus determine how the LCOE obtained by a deterministic approach is affected. To carry out this task, we employ two techniques based on stochastic differential equations to generate wind power scenarios. Utilizing 40 years of recorded wind speed data sourced from the MERRA-2 reanalysis, we derive the input parameters of the models from fitting to 4-parameter Dagum and Johnson SB probability distributions, which shows that accurate modeling of offshore wind speeds requires dealing with complex mathematical functions that need numerical computation. The findings show that the stochastic approach can estimate an uncertainty interval around the result obtained via the deterministic approach. In the case studies examined, the maximum and minimum values correspond to approximately ±1.6% and ±3.5% from the deterministic LCOE.